Marker-Assisted Selection for Pollen-Free Somatic Plants of Sugi (Japanese Cedar, Cryptomeria japonica): A Simple and Effective Methodology for Selecting Male-Sterile Mutants With ms1-1 and ms1-2 - Tsuruta, Momi; Maruyama, Tsuyoshi E.; Ueno, Saneyoshi; Hasegawa, Yoichi; Moriguchi, Yoshinari (Frontiers in Plant Science, 2021)
Pollen allergy caused by sugi (Japanese cedar, Cryptomeria japonica) is a serious problem in Japan. One of the measures against pollinosis is the use of male-sterile plants (MSPs; pollen-free plants). In this context, the development of a novel technique for the efficient production of sugi MSPs, which combines marker-assisted selection (MAS) with somatic embryogenesis (SE), was recently reported by our research group. To improve the efficiency of MSP production, in this paper we report improved MAS for male-sterile individuals from embryogenic cells, cotyledonary embryos, and somatic plants of sugi using a newly developed marker in the form of the causative mutation of MS1 itself, selecting individuals with ms1-1 and ms1-2 male-sterile mutations. We also describe simplified methods for extracting DNA from different plant materials and for MAS using LAMP diagnostics. Finally, we show that MAS can be efficiently performed using the one-step indel genotyping (ING) marker developed in this study and using InstaGene for DNA extraction. The combination of SE and 100% accurate marker selection during the embryogenic cell stage enables the mass production of MS1 male-sterile sugi seedlings.